2011
DOI: 10.1182/blood-2010-11-320317
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the regulatory mechanism controlling the inhibition of vaccine-induced seroconversion by maternal antibodies

Abstract: The inhibition of vaccination by maternal antibodies is a widely observed phenomenon in human and veterinary medicine. Maternal antibodies are known to suppress the B-cell response. This is similar to antibody feedback mechanism studies where passively transferred antibody inhibits the B-cell response against particulate antigens because of epitope masking. In the absence of experimental data addressing the mechanism underlying inhibition by maternal antibodies, it has been suggested that epitope masking expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 48 publications
2
66
0
Order By: Relevance
“…Nevertheless, inhibition of B cell responses can also be mediated by binding Fc region of passive antibody-vaccine Ag complex to the B cell Fcg-receptor IIB, results in a stronger negative signal that inhibits both the proliferation 21 and the antibodies secretion of B cells. 20 In this study, we observed a 9-fold increase in plasma anti-TT-IgG at 1 wk after three doses of primary immunizations (at 1.5, 2.5 and 3.5 mo of age), while at 1 y of age, it was decreased by about 5-fold from the peak and had returned to the pre-vaccination level (Fig. 1A).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, inhibition of B cell responses can also be mediated by binding Fc region of passive antibody-vaccine Ag complex to the B cell Fcg-receptor IIB, results in a stronger negative signal that inhibits both the proliferation 21 and the antibodies secretion of B cells. 20 In this study, we observed a 9-fold increase in plasma anti-TT-IgG at 1 wk after three doses of primary immunizations (at 1.5, 2.5 and 3.5 mo of age), while at 1 y of age, it was decreased by about 5-fold from the peak and had returned to the pre-vaccination level (Fig. 1A).…”
Section: Discussionsupporting
confidence: 52%
“…However, experimentally it has been shown that one antibody at a high concentration is less efficient in inhibiting active vaccination response than several antibodies at lower concentrations. 20 Presumably natural infection produced a more diverse array of antibodies than vaccines in the subclinical maternal pertussis infection as observed in our study. Nevertheless, inhibition of B cell responses can also be mediated by binding Fc region of passive antibody-vaccine Ag complex to the B cell Fcg-receptor IIB, results in a stronger negative signal that inhibits both the proliferation 21 and the antibodies secretion of B cells.…”
Section: Discussionmentioning
confidence: 49%
“…Three facts argue against this hypothesis: maternal antibodies suppress not only replicating live-attenuated vaccines but also (non-replicating) protein vaccines; immunization with vector systems expressing measles virus proteins (which are not sensitive to neutralizing antibodies) are inhibited by maternal antibodies (134136); and non-neutralizing antibodies block vaccination with a live-attenuated vaccine (114). …”
Section: Mechanisms Of Inhibition Of Vaccination By Maternal Antibodiesmentioning
confidence: 99%
“…This solution appears to be impossible to achieve in the presence of high levels of maternal antibody and an increase in vaccine dose would probably be harmful (as in the case of measles vaccination [8][9][10]). Using the cotton rat model of MV vaccination [16], we have now established that inhibition by maternal antibody is due to cross-linking of the B-cell receptor (BCR) and FcgIIB receptor by a measles virus-antibody (IgG) complex [17]. Thus, maternal antibodies trigger a regulatory mechanism of B-cell responses similar to that used by IgG antibodies after active immunization.…”
Section: Mechanism Of Inhibition By Maternal Antibodiesmentioning
confidence: 94%
“…In an enzyme-linked immunosorbent spot assay, MV-specific IgM stimulates B cells to secrete antibody even in the presence of inhibitory IgG. After coimmunization of MV vaccine and a monoclonal IgM antibody specific for MV hemagglutinin in the presence of maternal antibodies, neutralizing antibodies were restored to approximately 20-40% of antibody levels after immunization in the absence of maternal antibodies [17]. Another approach has focused on the induction of a third signal because MV vaccine virus does not induce type I interferon secretion by dendritic cells in tissue culture, or in the bronchoalveolar lavage in cotton rats [18].…”
Section: Improving Vaccination In the Presence Of Maternal Antibodiesmentioning
confidence: 96%